2021
DOI: 10.1371/journal.pone.0261110
|View full text |Cite
|
Sign up to set email alerts
|

Upright epiglottis prevents aspiration in patients with nasopharyngeal carcinoma post-chemoradiation

Abstract: NPC is the most widely found malignant tumor in the head and neck region in Indonesia. Chemoradiation therapy for NPC can induce swallowing disorders (dysphagia) that adversely affects a patients quality of life. This study aimed to assess the swallowing process by flexible endoscopic evaluation of swallowing in patients with nasopharyngeal carcinoma after chemoradiation. Thirty-nine patients with NPC who had chemoradiation therapy more than one month previously underwent flexible endoscopic evaluation of swal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The application of kareolizumab means that immunotherapy for nasopharyngeal carcinoma has entered a new era, and the progresses in molecular biology and bioengineering technology have enabled the immunotherapy methods to gradually increase. CIK is a new type of immunocompetent cell that can be used for nasopharyngeal carcinoma treatment [ 23 ]. CIK cells are the T cells obtained by cultivating human peripheral blood mononuclear cells with various cytokines and are characterized with broad tumoricidal spectrum and high efficiency in killing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The application of kareolizumab means that immunotherapy for nasopharyngeal carcinoma has entered a new era, and the progresses in molecular biology and bioengineering technology have enabled the immunotherapy methods to gradually increase. CIK is a new type of immunocompetent cell that can be used for nasopharyngeal carcinoma treatment [ 23 ]. CIK cells are the T cells obtained by cultivating human peripheral blood mononuclear cells with various cytokines and are characterized with broad tumoricidal spectrum and high efficiency in killing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation to the head and neck is known to cause swallowing dysfunction, as well as anatomic changes in the epiglottis due to fibrosis and edema. [25][26][27][28][29] Cervical spine osteophytes or spinal hardware may impinge into the pharyngeal lumen and prevent epiglottic inversion. 11,30,31 Seo et al showed that maximal epiglottic angular velocity was lower in stroke patients, and that a decreased maximal epiglottic tilt angle, and decreased maximal epiglottic angular velocity were associated with increased risk of aspiration in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tamin 30 stated that microtrauma in the tonsil basal cell epithelia due to repetitive acid and pepsin exposure serves as an entry point for the infiltration of human papillomavirus (HPV), especially subtypes 6 or 11. This results in partial suppression of the early viral gene, which stimulates the proliferation of basal cells and leads to lateral expansion and hypertrophy of the cells.…”
Section: Discussionmentioning
confidence: 99%